Optimal combination of early biomarkers for infection and sepsis diagnosis in the emergency department: The BIPS study. Issue 4 (April 2021) - Velly, Laetitia; Volant, Steven; Fitting, Catherine; Ghazali, Daniel Aiham; Salipante, Florian; Mayaux, Julien; Monsel, Gentiane; Cavaillon, Jean-Marc; Hausfater, Pierre
Highlights: Combination of plasma and cell surface biomarkers are useful to discriminate suspected infected patients. Combination of HLA-DR, Mertk and MMP8 is performant for bacterial infection diagnosis. Combination of CD64, CD24 and CX3CR1 is performant for viral infection diagnosis. Combination of HLA-DR, PCT and IL-6 is performant for sepsis-2 diagnosis. Abstract: Objective: : To define the best combination of biomarkers for the diagnosis of infection and sepsis in the emergency room. Methods: : In this prospective study, consecutive patients with a suspicion of infection in the emergency room were included. Eighteen different biomarkers measured in plasma, and twelve biomarkers measured on monocytes, neutrophils, B and T-lymphocytes were studied and the best combinations determined by a gradient tree boosting approach. Results: : Overall, 291 patients were included and analysed, 148 with bacterial infection, and 47 with viral infection. The best biomarker combination which first allowed the diagnosis of bacterial infection, included HLA-DR (human leukocyte antigen DR) on monocytes, MerTk (Myeloid-epithelial-reproductive tyrosine kinase) on neutrophils and plasma metaloproteinase-8 (MMP8) with an area under the curve (AUC) = 0.94 [95% confidence interval (IC95): 0.91;0.97]. Among patients in whom a bacterial infection was excluded, the combination of CD64 expression, and CD24 on neutrophils and CX3CR1 on monocytes ended to an AUC = 0.98 [0.96;1] to define those with a viral infection. Conclusion: : In a convenient cohort of patients admitted with a suspicion of infection, two different combinations of plasma and cell surface biomarkers were performant to identify bacterial and viral infection.